Neurofilament Light Chain in Serum and CSF as a Potential Biomarker for Primary Angiitis of the Central Nervous System - Christina Krüger; Hans Pinnschmidt; Maximilian Wilmes; Justina Dargvainiene; Frank Leypoldt; Alexander Seiler; Daniela Berg; Tim Magnus; Milani Deb-Chatterji (Cells, 2025)
Background: Primary angiitis of the central nervous system (PACNS) is a rare vasculitis affecting CNS blood vessels, posing diagnostic challenges due to the limited specificity of the established diagnostic tools. Neurofilament light chain (NfL) might be a promising biomarker in PACNS. Methods: NfL in serum and CSF was measured in 33 PACNS patients (25 active [aPACNS], 8 in remission [rPACNS]) enrolled between 2014 and 2022 and compared to controls (serum: n = 303; CSF: n = 68); Results: Serum NfL was significantly elevated in aPACNS (median: 45.77 pg/mL) versus rPACNS (6.68 pg/mL; p < 0.001) and healthy controls (6.05 pg/mL; p < 0.001). Similarly, CSF NfL was significantly elevated in aPACNS (median: 4914.58 pg/mL) compared to rPACNS (301.19 pg/mL; p = 0.002) and controls (262.83 pg/mL; p < 0.001). Serum and CSF NfL were significantly correlated (r = 0.90, p < 0.001). Additionally, an association between elevated NfL and ischemic lesions was observed (serum: r = 0.59, p = 0.006; CSF: r = 0.43, p = 0.032). A subgroup analysis excluding stroke patients still revealed elevated NfL in 90% (CSF) and 50% (serum), with diminishing discriminatory power with older age. Conclusions: NfL holds potential as a biomarker for PACNS, in particular in younger patients.